(untitled) (Research, Society and Development, 2022)
Artocarpus heterophyllus is an invasive exotic species known for its negative impacts on Brazilian ecosystems. The aim of this study was to evaluate the distribution and population structure of A. heterophyllus in the plant community of a forest fragment in the Amazon. Individuals of this species were subject to active search at Sumaúma State Park, in Manaus, and two plots were delimited, where these individuals were counted. In each plot, the jackfruit tree individual with the largest Diameter at Breast Height (DBH) was centralized, and from it, native species were inventoried. The parameters of relative density, relative dominance and the importance value index were estimated. Jackfruit tree individuals in the plots had grouped distribution and their number in plots 1 and 2 was 308 and 872 individuals, respectively. In quadrant 1, 254 jackfruit trees and 118 native individuals were recorded, and in quadrant 2, 629 jackfruit and 130 native individuals. The jackfruit tree reached indices higher than the sum of the phytosociological indices of all native species. Jackfruit tree distribution was considered similar to that occurring in other already invaded areas of Brazil, which may indicate that the same impacts may occur in Amazonian ecosystems.